Physical and Paste Properties Comparison of Four Snacks Produced by High Protein Quinoa Flour Extrusion Cooking - Muñoz-Pabon, Karen Sofia; Parra-Polanco, Astrid Soraya; Roa-Acosta, Diego Fernando; Hoyos-Concha, Jose Luis; Bravo-Gomez, Jesus Eduardo (Frontiers in Sustainable Food Systems, 2022)
Extrusion cooking is used to produce puffed snacks based on cereals and feed ingredients. Because of its nutritional properties, quinoa flour has been employed to prepare various types of foods. This study evaluates the effects of including hyper-protein quinoa flour obtained through abrasive milling in four formulations cooked at 27% moisture content and processed in a laboratory level single screw extruder to determine their physical, textural, and pasting properties. The results indicated that additional hyper-protein quinoa flour in the cereal mixture reduced 47% the expansion index (EI), while the extrudate density (ED) and hardness increased 54 and 130%, respectively. After the extrusion process, the water absorption index (WAI), water solubility index (WSI) increased by more than 100%. The addition of hyper-protein quinoa flour (25–37%) did not affect the WAI, but an increase in the WSI was observed. The quinoa flour extrusion process generated changes on the color mainly in the L parameter, which decreased in the extruded snacks with quinoa flour inclusion (51.49), compared to the snack without inclusion (62.68). Changing the integrity of the starch granules and associated proteins, causing a decrease in the viscosity peaks during heating and subsequent cooling. The extruded samples revealed stability in the retrogradation process. Extruded snacks from quinoa could be an alternative approach to produce feed ingredients with high protein contents.